A Study of Contemporary Pashto Ghazal of Malakand in the Context of Environmental Pollution - Rahman, Ibad Ur; Aman, Noor Ul Basar (Makhz (Research Journal), 2025)
Ecocriticism sets up an association between humans and the natural environment and pleads solutions to the problems faced by the natural world. Environmental pollution is one of the fabulous ecological consequences of our time, and human beings are responsible for it. Pollution exists in many forms, including land pollution, water pollution, air pollution, noise pollution, chemical pollution, and nuclear pollution. This article will examine and highlight various aspects of the environmental pollution mentioned in the contemporary Pashto ghazal of Malakand Division.